Therapy with sodium stibogluconate in stearylamine-bearing liposomes confers cure against SSG-resistant Leishmania donovani in BALB/c mice. - Jayeeta Roychoudhury; Roma Sinha; Nahid Ali (PLoS ONE, 2011)
BACKGROUND: Resistance of Leishmania donovani to pentavalent antimonials, the first-line treatment of visceral leishmaniasis (VL), has become a critical issue worldwide. Second-line and new drugs are also not devoid of limitations. Suitable drug-delivery systems can improve the mode of administration and action of the existing antimonials, thus increasing their clinical life. METHODOLOGY/PRINCIPAL FINDINGS: We investigated the efficacy of sodium stibogluconate (SSG) in phosphatidylcholine (PC)-stearylamine-bearing liposomes (PC-SA-SSG), PC-cholesterol liposomes (PC-Chol-SSG) and free amphotericin B (AmB) against SSG-resistant L. donovani strains in 8-wk infected BALB/c mice. Animals were sacrificed and parasites in liver, spleen and bone marrow were estimated 4-wk post-treatment by microscopic examination of stamp smears and limiting dilution assay. A set of PC-SA-SSG and AmB treated mice were further studied for protection against reinfection. Serum antibodies and cytokine profiles of ex-vivo cultured splenocytes were determined by ELISA. Uptake of free and liposomal SSG in intracellular amastigotes was determined by atomic absorption spectroscopy. Rhodamine 123 and 5-carboxyfluorescein, known substrates of Pgp and MRP transporter proteins, respectively, were used in free and liposomal forms for efflux studies to estimate intracellular drug retention. Unlike free and PC-Chol-SSG, PC-SA-SSG was effective in curing mice infected with two differentially originated SSG-unresponsive parasite strains at significantly higher levels than AmB. Successful therapy correlated with complete suppression of disease-promoting IL-10 and TGF-β, upregulation of Th1 cytokines and expression of macrophage microbicidal NO. Cure due to elevated accumulation of SSG in intracellular parasites, irrespective of SSG-resistance, occurs as a result of increased drug retention and improved therapy when administered as PC-SA-SSG versus free SSG. CONCLUSIONS/SIGNIFICANCE: The design of this single-dose combination therapy with PC-SA-SSG for VL, having reduced toxicity and long-term efficacy, irrespective of SSG-sensitivity may prove promising, not only to overcome SSG-resistance in Leishmania, but also for drugs with similar resistance-related problems in other diseases.